Feasibility and acceptance of a Cloud-based mobile app for antimicrobial stewardship and infection prevention in Colombian hospitals - Ketcherside, William J; Olson, Jonathan BF; Hunt, Lauren N; Mehta, Jimish M; Gutiérrez, Christian Pallares; Coy, Lina Marcela; Pradera, Iñigo Prieto; Rivera, Ayleen D; Cano, Jorge A; Saeed, Alex; Sapiro, Vadim; Park, Benjamin J; et al. (International Journal of Infection Control, 2020)
Infection Control and Antimicrobial Stewardship Programs (ICASPs) are essential to reduce the emergence and spread of antimicrobial resistance. The primary objective of this study was to assess the feasibility of extending a commercial off-the-shelf (COTS) software for ICASPs in LMICs. This project involved three hospitals in Colombia, including Centro Médico Imbanaco, Clínica San Francisco, and DIME Clínica Neurocardiovascular. A COTS platform (ILÚM Health Solutions™; Kenilworth, NJ) was extended to function in a range of technology settings, and translatable to almost any language. ICASP features were added, including clinical practice guidelines, hand hygiene (HH) documentation, and isolation precaution (IP) documentation. The platform was delivered as a smartphone app for both iOS and Android. The app was successfully implemented at all sites, however, full back-end data integration was not feasible at any site. In contrast to the United States, a suite of surveillance tools and physician-focused decision support without patient data proved to be valuable. Language translation processing occurred quickly and incurred minimal costs. HH and IP compliance tracking were the most used features among ICASP staff; treatment guidelines were most often used by physicians. Use of the app streamlined activities and reduced the time spent on ICASP tasks. Users consistently reported positive impressions including simplicity of design, ease of navigation, and improved efficiency. This ICASP app was feasible in limited-resource settings, highly acceptable to users, and represents an innovative approach to antimicrobial resistance prevention.